3-Total edge product cordial labeling of complete, bipartite and generalized friendship Graphs - Azaizeh A.; Hasni R.; Lau G.C.; Ahmad A. (Utilitas Mathematica, 2018)
For a graph G = (E(G))y an edge labeling function / : E(G)→ {0,1, - , fc - 1} where k is an integer, 2 < k < |£(C?)|, induces a vertex labeling function f∗ : V(G) → {0,l,... ,fc - 1} such that f∗(v) is the product of the labels of the edges incident to v (mod k). This function / is called a fc-Total edge product cordial labeling of G if I Mi) + e/(i)) - (vf(j) + e/(j))| < 1 for all ij ϵ {0, 1,... ,fc - 1}. In this paper, 3-Total edge product cordial labeling of complete, bipartite and generalised friendship graphs is determined. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.